Banquet at the U.S. Consul for the July 4th celebration, Dawson, Yukon Territory, 1899. - Hegg, Eric A., 1867-1948 (1899)
Caption on image: "Banquet by the U.S. Consul Dawson July 4th 99" Original photograph by Hegg 2360; copied by Larss and Duclos.